2015
DOI: 10.1007/978-3-662-47824-0_6
|View full text |Cite
|
Sign up to set email alerts
|

New Nonlinear CPRNG Based on Tent and Logistic Maps

Abstract: This paper is devoted to the design of new chaotic Pseudo Random Number Generator (CPRNG). Exploring several topologies of network of 1-D coupled chaotic mapping, we focus first on two dimensional networks. Two coupled maps are studied: T T L RC non-alternative, and T T L SC alternative. The primary idea of the novel maps has been based on an original coupling of the tent and logistic maps to achieve excellent random properties and homogeneous /uniform/ density in the phase plane, thus guaranteeing maximum sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In this chapter, we thoroughly explored the novel idea of combining features of a tent map (T µ ) and a logistic map (L µ ) to produce a new map with improved properties, through combination in several network topologies. This idea was recently introduced [38,39] in order to improve previous CPRNGs. We have summarized the previously explored topologies in dimension two.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this chapter, we thoroughly explored the novel idea of combining features of a tent map (T µ ) and a logistic map (L µ ) to produce a new map with improved properties, through combination in several network topologies. This idea was recently introduced [38,39] in order to improve previous CPRNGs. We have summarized the previously explored topologies in dimension two.…”
Section: Resultsmentioning
confidence: 99%
“…The second condition is that the CPRNG must be assessed positively by the NIST tests [40]. In [38,39] this two-dimensional case is studied in detail. Using a bifurcation diagram and computation of Lyapunov exponents, it is shown that the best value for the parameter is µ = 2.…”
Section: Two-dimensional Network Topologiesmentioning
confidence: 99%
See 3 more Smart Citations